2015
DOI: 10.1080/19460171.2015.1014519
|View full text |Cite
|
Sign up to set email alerts
|

A narrative-interactionist approach to policy change analysis. Lessons from a case study of the cultural policy domain in Catalonia

Abstract: The cultural policy domain can be considered a relevant object of study for analyzing policy change processes in which policy discourse and the ambiguity of language have a central role. However, there are few studies that analyze cultural policy and policy change. This article therefore develops an approach for analyzing policy change based on evidence from a case study of the development of cultural policy in Catalonia. In this narrative interactionist approach, policy change is taken to mean the result of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
10

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
5
0
10
Order By: Relevance
“…These policy activities occur in political institution. Thus, authoritarian institutions, characterised by an uneven distribution of power, affect not only the rules of the game and the creation of new actors but also policy priorities, issue framing, discourse and the generation of new areas (Schmidt 2008;Mahoney and Thelen 2010;Radadelli et al 2012;Barbieri 2015). The influence of institutions on the development of conflict and policy change process is significant and large.…”
Section: Conflict Expansion and Policy Change In Authoritarian Regimesmentioning
confidence: 99%
“…These policy activities occur in political institution. Thus, authoritarian institutions, characterised by an uneven distribution of power, affect not only the rules of the game and the creation of new actors but also policy priorities, issue framing, discourse and the generation of new areas (Schmidt 2008;Mahoney and Thelen 2010;Radadelli et al 2012;Barbieri 2015). The influence of institutions on the development of conflict and policy change process is significant and large.…”
Section: Conflict Expansion and Policy Change In Authoritarian Regimesmentioning
confidence: 99%
“…The potential and importance of the analysis of policy frames is supported by its increasing use in the study of processes and trajectories of public policies in areas such as gender policies (Lombardo & Meier, 2009; Verloo, 2005); migration (Roggeband, 2010); cultural policies (Barbieri, 2015); social movements and collective action (Benford & David, 2000), among others, thus accumulating an increasing volume of empirical evidence (Roberts, 2016; Shim, Park, & Wilding, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 While it is only right to mention the key factors in structuring cultural policy, these schemes need to be compared in each context. This is because the literature has shown that the political agenda can also be based on other variables and interests, such as economic and political instrumentalisation (Barbieri, 2015;Gray, 2008;Parker and Parenta, 2009). Various agency factors have been shown to be determinants in the orientation and transformation of cultural policies.…”
Section: Models Of Cultural Policies and The Evolution Of Cultural Mamentioning
confidence: 99%